Dynamic Moves: A Case Study of Eleventh Graders in One Senior High School in Bandung - Wahyuni, Dini Sri (2013)
Interaction is an important word for language teacher. The interaction between teacher and students can determine the quality of teaching learning. In some instances of classroom interaction, the occurrence of dynamic moves cannot be avoided. The dynamic elements may always be found in the interaction between teacher and students. Moreover, teacher plays many roles in the interaction; one of them is the initiator of interaction. Interaction can be initiated by asking question or giving instruction to the students. The research was aimed to find out types of dynamic moves in the classroom interaction and to reveal how teacher's questions and instructions affect the occurrence of dynamic moves. An English teacher and 38 eleventh graders of a public senior high school in Bandung served as respondents. The data derived from video recording and interviews were analyzed using dynamic moves theory developed by Martin (1985), Ventola (1987) and Suherdi and Love (1996 cited in Suherdi, 2009). Besides that, questions and instructions used by the teacher are categorized. The instruction are categorized based on FLINT theory proposed by Moskowitz (1971 cited in Brown, 2001), while the question are categorized into some category proposed by Kinsella (1991) and Bloom (1956 cited in Brown, 2001). The findings revealed that almost all types of dynamic moves were found in the interaction, except backchanneling. The phenomena of dynamic moves frequently occurred in knowledge questions and it increased when the teacher applied another questions, namely comprehension question and analysis question. However, the teacher's instruction such as giving information, giving direction and criticizing students' behavior gave low contribution to the variation of dynamic moves in the classroom interaction. It is recommended that further research involves several teachers to give rich information especially for the teachers in improving their performing in creating communicative interaction or further research can be also conducted n different lesson that is not the same with this research. Keywords: Classroom interaction, Dynamic moves, Teacher's questions, Teacher's instructions.